Pengaruh Hedonik Value, Store Atmosphere dan Promosi terhadap Keputusan Pembelian Konsumen Pada Pizza Hut di Kedai Rilex Jember - Mochamad Alfan Firmansyah; Ni Nyoman Putu Martini; Tatit Diansari Reskiputri (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This research was conducted on consumers of Pizza Hut at Kedai Rilex Jember. This study aims to determine the influence of hedonic value, store atmosphere, and promotion on purchasing decisions at Pizza Hut At Kedai Rilex Jember. In this study, data were collected with tools in the form of observation, interviews, and questionnaires for 100 respondents using purposive sampling techniques. The analysis used includes data instrument tests (validity tests, and reliability tests), multiple linear regression analysis, classical assumption tests (normality test, multicholinearity test, heteroskedasticity test), and hypothesis test (F test, t test, coefficient of determination). From the results of the analysis using regression, it can be seen that the variables hedonic value (0.230), mood (0.285), and promotion (0.262), all have a positive effect on purchasing decisions. From the t test, hedonic value results (0.001) had a significant effect on purchasing decisions. The mood test (0.000) has a significant effect on purchasing decisions. As well as promotions (0.000), all have a significant effect on purchasing decisions. From the results of the study, it can be concluded that the better the hedonic value will have an impact on the better the purchase decision, the better the store atmosphere will have an impact on the better the purchase decision and the promotion affects the purchase decision which means that the better the promotion will have an impact on the better the purchase decision. Keywords: Hedonic Value, Purchase Decision, Promotion and Atmosphere